Respuesta :
- <AEB=<CED
[tex]\\ \rm{:}\dashrightarrow 4x+1=3x[/tex]
[tex]\\ \rm{:}\dashrightarrow 4x-3x=1[/tex]
[tex]\\ \rm{:}\dashrightarrow x=1[/tex]
Now
[tex]\\ \rm{:}\dashrightarrow 3x=3(1)=3[/tex]
[tex]\\ \rm{:}\dashrightarrow 4x+1=4(1)+1=5[/tex]
Answer:
AEB = -3
CED = -3
Step-by-step explanation:
We can make an equation and solve for x.
4x + 1 = 3x
~Subtract 1 to both sides
4x = 3x - 1
~Subtract 3x to both sides
x = -1
Now we can substitute that value of x into both angles.
4(-1) + 1 = -4 + 1 = -3
3(-1) = -3
Best of Luck!